التأمين التكافلي كأحد الاستراتيجيات للحد من المخاطر التأمينية: نموذج التجربة الماليزية - برغوث, أسامة; ضربان, فاطنة (جامعة الوادي - University of Eloued, 2024)
يمثل التأمين التكافلي إحدى الاستراتيجيات التي يمكن استخدامها في إدارة المخاطر، والتي تتميز بالتعاون والتضامن بين المشتركين، يتضمن هذا النوع من التأمين تغطية شاملة للمصاريف المتعلقة بالرعاية الصحية والوفاة والمسؤولية المدنية، يتم إدارة المخاطر بشكل دقيق للحد من التبعات السلبية المرتبطة بالحوادث والكوارث الطبيعية والأمراض وغيرها من الأحداث التي يمكن أن تؤثر على حياة المشتركين، إستعرضنا من خلال هذه الدراسة التجربة الماليزية التي تعتبر نموذجا يقتدى به، بنجاحها في إستخدام التأمين التكافلي كإستراتيجية للحد من المخاطر التأمينية. Takaful insurance represents one of the strategies that can be used in risk management, which is characterized by cooperation and solidarity among the participants. This type of insurance includes comprehensive coverage of expenses related to health care, death and civil liability. Risks are managed accurately to reduce the negative consequences associated with accidents, natural disasters, diseases and other Events that can affect the lives of the subscribers, we reviewed through this study the Malaysian experience, which is considered a role model, with its success in using Takaful insurance as a strategy to reduce insurance risks.
Takaful insurance as one of the strategies to reduce insurance risks: the Malaysian experience model
مقال
Keywords: إدارة المخاطر التأمينية ; شركات التأمين ; التأمين التكافلي ; التجربة الماليزية; insurance risk management, insurance companies, Takaful insurance, the Malaysian experience.